Principles of Organizing Self-directed Learning of First-year Students within the Flipped Classroom Technology - T. A. Borzova (Высшее образование в России)
The quality of professional education depends on the effectiveness of educational technologies. The Flipped Classroom technology is being  successfully tested at the Russian Language Department of Vladivostok State University of Economics and Service within the “Russian Language and  Culture of Speech” course. The article analyzes the experience of teaching with the use of the Flipped Classroom technology; it discusses the  special features of teaching first-year students, and the principles for  organization of self-directed learning process. In flipped learning, self- directed learning is the dominating type of educational activity. Teachers  must prepare their students for self-directed learning in the Moodle electronic educational environment, they must motivate them to independently master  the theoretical material and to do the practical and controlling assignments  and tests. In mixed education, self-directed learning helps to intensify the  educational process; forms first-year students’ self-education skills; develops  such important personal qualities as independence, activity,  consciousness and responsibility. When organizing self-directed learning of students, special attention should be given to the development of practical assignments for testing and control. In teaching the “Russian Language and  Culture of Speech” course, the following interactive and electronic tasks are  used to form skills and abilities in a reproductive, reconstructive, and creative performance: essays, glossary, mutual reviews, business games, projects, etc. Active methods of control and an electronic survey at the end  of the course facilitate the optimization of the self-directed learning process. Considering the special features of mixed education of first-year students,  the author defines the main principles for organizing self-directed learning.  They are continuity and systematicity; regularity and rhythm; intensity and  optimality of workload; interactivity, individualization, feedback and control;  effectiveness of activity; development of self-educational skills and such personal qualities as independence, activity, consciousness and responsibility.